2020
DOI: 10.1037/hea0000864
|View full text |Cite
|
Sign up to set email alerts
|

Parental behavior and child distress and pain during pediatric medical procedures: Systematic review and meta-analysis.

Abstract: Objective: In this study review, the relationship between observed parental behavior and the observed symptoms of distress in pediatric patients, as well as the subjective experiences of pain in pediatric patients undergoing painful medical procedures, was analyzed. Method: A systematic search of articles using PsycARTICLES, PsycINFO, PubMed, MEDLINE, Scopus, Cochrane, and DARE was performed. The risk of bias and the level of evidence were assessed. Meta-analyses were performed for the selected variables. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…According to the International Association for the Study of Pain, “pain is always a personal experience that is influenced to varying degrees by biological, psychological, and social factors” [ 1 ]. Studies estimate that as many as half of children with acute or chronic illnesses experience procedure-related pain and distress [ 2 ]. In the short term, pain can manifest as withdrawal, clinginess, moodiness, or anger.…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Association for the Study of Pain, “pain is always a personal experience that is influenced to varying degrees by biological, psychological, and social factors” [ 1 ]. Studies estimate that as many as half of children with acute or chronic illnesses experience procedure-related pain and distress [ 2 ]. In the short term, pain can manifest as withdrawal, clinginess, moodiness, or anger.…”
Section: Introductionmentioning
confidence: 99%
“…The definition, connotation, and extension of children in difficulty are a controversial issue in academic circles. In academic research, scholars use a broader concept, which refers to all children whose survival and development are in trouble because of poverty, disease, accident, neglect, and family abuse (Sobol-Kwapińska et al, 2020 ). The early concept of children in plight comes from the description in child welfare policy of international organizations, such as “children living in extreme distress (Hoyt et al, 1997 ).” Moreover, terms such as “special needs”, “special hardship”, “social disadvantage”, “most vulnerable”, and “in need of help” vary from time to time, which express the life situation of children in difficulties (Benn et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For our first objective, we expected that previously demonstrated relations between parent behavior and child behavior 4,6,18,28,29 would be supported in this sample and extended to children's self-reports of pain and fear. For example, individual parent "coping promoting" behaviors (i.e., distraction, humor, commands to engage in a coping strategy), and "distress promoting" behaviors (i.e., reassurance, giving control to the child, apology, empathy, criticism) would be associated with increased and decreased child coping in this sample, respectively.…”
Section: [Insert Figure 1 Here]mentioning
confidence: 99%
“…14,17 In the context of painful procedures, parent empathy emerged as a strong predictor of children's distress and pain in a recent meta-analysis. 18 However, nuances in these relations, such as the role of parent state distress in the association of parent empathy and child outcomes, are not well understood. For example, Emery and colleagues 16 demonstrated that maternal empathy was related to increased sensitivity to their children when mothers were reporting low, and not high, negative emotional reactivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation